Epilepsy is not statistically associated with systemic sclerosis but significantly impacts on mortality: A real-world epidemiological survey-based study. Issue 5 (October 2018) - Watad, Abdulla; Bragazzi, Nicola Luigi; Brigo, Francesco; Adawi, Mohammad; Mahroum, Naim; Comaneshter, Doron; Amital, Daniela; Cohen, Arnon D.; Amital, Howard
Abstract: Little is known about the relationship between epilepsy and SSc. Our study included 2431 SSc patients and 12, 710 age- and sex-matched controls. In 209 controls (1.6%) and 66 SSc patients (2.7%), epilepsy diagnosis was made (not significant). In the multivariate logistic regression analysis, higher age (OR 1.01 [95% CI 1.00–1.02], p = 0.0207) was associated with an increased risk of epilepsy, whereas high vs low socioeconomic status (SES) (OR = 0.62 [95% CI 0.42–0.92], p = 0.0189) was associated with a low risk of epilepsy. In the Cox multivariate survival analysis, higher age (HR = 1.06 [95% CI 1.06–1.07], p < 0.0001), epilepsy (HR = 2.28 [95% CI 1.77–2.94], p < 0.0001) and SSc (HR = 2.37 [95% CI 2.07–2.71], p < 0.0001) were independent risk factors for all-cause mortality. In contrast, BMI >30 kg/m 2 vs BMI <20 kg/m 2 (HR = 0.69 [95% CI 0.59–0.81, p < 0.0001]), female gender (HR = 0.73 [95% CI 0.65–0.83], p < 0.0001) and high SES (HR = 0.72 [95% CI 0.63–0.82], p < 0.0001) were protective factors for mortality. SSc-related autoantibodies were not associated with the risk of epilepsy. In conclusion, whilst epilepsy and SSc are not significantly associated, epilepsy is a predictor of mortality in SSc patients.